Homeownership “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS)
This publication discusses general information about home buying, military-specific housing decisions, military-specific home buying, and home-buying tips for military families. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.